INTERNAL FACTORS AFFECTING THE ADHERENCE OF ANTIRETROVIRAL (ARV) THERAPY OF PATIENTS WITH HIV/AIDS IN RSUD KOTA BOGOR - Ajeng Sekar Dewanty; Dewi Purnamawati (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Antiretroviral (ARV), as the primary therapy, plays an essential role in preventing the risk of opportunistic infections and increasing the quality of life patients with HIV. The main purpose of the ARV program treatment affected the patient’s health behavior, namely the adherence to consuming ARV daily. This study tries to elaborate on some internal factors that can affect patient compliances to finishing ARV. The study was conducted at RSUD Kota Bogor on 94 patients. The variables were classifiedased on age group, gender, level of education, work history, and compliance status Furthermore, an analysis was carried out to determine the factors affecting ARV compliance. The study showed that there were 84.2% (16) males, 68.4% (13) aged > 25 y.o, 73.7% (14) with low education, and 57.9% (11) jobless patients with a low level of adherence. In summary, this study showed that internal factors, such as age, gender, education, and occupation, are descriptively related to the level of compliance as advice analytical study with other factors was needed.